The Dynamics of Type 2 Diabetes Mellitus Prevalence and Management Rates among Rural Population in Henan Province, China - Xiaotian Liu; Ling Wang; Panpan Wang; Ruihua Liu; Kaili Yang; Xinling Qian; Jingjing Fan; Songcheng Yu; Yuqian Li; Chongjian Wang (Journal of Diabetes Research)
The aim of this study was to estimate the dynamics of type 2 diabetes mellitus (T2DM) prevalence and management rates based on a rural cohort study in Henan Province of China. The rural prospective study was conducted for 20194 Chinese population ≥18 years in 2007-2008 and followed during 2013-2014. A total of 14009 individuals were recruited for the prospective analysis ultimately. Over 5.74 years of follow-up, the age-standardized prevalence, awareness, treatment, and control of T2DM increased from 6.18%, 44.41%, 34.39%, and 19.08% at baseline to 7.87%, 59.64%, 52.17%, and 26.52% at follow-up in total population, respectively. Similar changes were found in men and women except the age-standardized control in men. The four parameters of T2DM were higher among various factors at follow-up than those at baseline. There was no statistical difference in awareness (P=0.089) and treatment (P=0.257) in the newly diagnosed T2DM compared with the rates at baseline. The current study indicated that the prevalence, awareness, treatment, and control of T2DM displayed chronological increasing trends while the awareness, treatment, and control of T2DM were still disproportionally low in central China. More works are needed urgently to popularize public health education and improve the quality of medical care in T2DM.